The Indication of the Monument of Names in the Reading of Zaid Bin Ali (T: 121 or 122 AH) (Peace be Upon them Both) - Karim, Dr. Abdul Hadi Kazem (International Journal of Psychosocial Rehabilitation, 2020)
The Title: The Importance of Assigning Names in the Quranic Reading of Zaid bin Ali bin Hussein bin Ali, the cousin of our Prophet, may God bless him and grant him peace. A number of Quranic Surahs. The recitations were arranged according to the order of the Quranic Surahs. The research showed that this reading coincides with. Principles of Arabic syntax. It simply exposes some rhetorical devices to recognize in the seven Qur’anic readings. Search after all the originality of the special treatment appears.